Perfil demográfico e condições sanitárias dos idosos em área urbana do Sudeste do Brasil - Telarolli Junior, Rodolpho [UNESP]; Machado, José Cândido M. S.; Carvalho, Fernanda (Universidade de São Paulo (USP), Faculdade de Saúde Pública, 1996)
São apresentadas séries históricas de indicadores demográficos e sanitários para a população com 60 anos e mais do Brasil, Estado de São Paulo e Município de Araraquara, de porte médio. em 1991, os idosos eram 7,8% da população brasileira e 9,7% de Araraquara, superando em número as crianças menores de 5 anos (8,9%). Aumentou o peso relativo do segmento com mais idade (70 anos e mais), que já representa 40% do total, assim como o índice de urbanização dos idosos, 93,7% no Estado e 96,3% no Município, acima da média da população em geral em 1991. As principais causas de morte são as doenças do aparelho circulatório (40% do total de óbitos) e os neoplasmas (15%). São sugeridas medidas para a assistência à saúde dos idosos: a) expansão da capacidade atual de atendimento, através do treinamento gerontológico de médicos generalistas e enfermeiros da rede pública e privada; b) incremento das atividades educativas já existentes, dirigidas aos idosos, profissionais da saúde e educadores do ensino médio; c) incremento do programa de visita domiciliar aos idosos e criação de hospital-dia para evitar internações necessárias e garantir a manutenção dos baixos níveis atuais de institucionalização em asilos (0,7% em Araraquara). A existência de pelo menos 35% dos idosos de Araraquara, com acesso à assistência privada à saúde, reforça a importância da inclusão desses serviços nos programas locais de saúde da terceira idade.

Some specific characteristics of the aging of the Brazilian population in different areas, states and communities all over the country, have shown significant variations. Historical series of demographic and health indicators for the population in their sixties and over in Brazil, state of S. Paulo and in the municipal district of Araraquara are listed as follows: level of education and urban population growth rate, income distribution, mortality rates and main causes of death. In 1991 the aged constituled were 7,8% of the Brazilian population and 9,7% in Araraquara community. The elderly population (of 70 years of aged and above) as a proportion of the whole, has increased and already stands for 40%. The same trend holds good for both the proportion of aged within the urban population and their level of education wich increased to 90% in 1991. The main causes of death are chronic degenerative diseases which have replaced the infectious illness: firts, the diseases of the circulatory sistem (which account for more than 40% of all deaths) and the neoplasms (which let to 15% of the deaths). on the basis of these health and demographic data relating to people of 60 years of age and over, this study suggests some procedures for the improvement of the quality of the assistance given to the target population: a) the assistance give to the aged should be improved by providing gerontological training for general physicians and nurses, both of public and private clinics; b) the already exixting educational activities for the aged, for health workers and for teachers of secundary education should be further developed; c) the number of day-hospitals should be increased for the purpose of avoiding unnecessary confinement so as maintain the low rate of institutionalization in homes for the elderly (0,7% in Araraquara). It is reported that at least 35% of the aged population in this area is entitled to private health assistance, wich brings out the importance of including such services in the local health programs for this group.
Demographic profile and health conditions of the elderly in a community in an urban area of Southeastern Brazil
Keywords: Envelhecimento da população; Necessidades e demanda de serviços de saúde; Saúde do idoso; Demographic aging; health services needs and demand; Aging health